Pengaruh Financial Distress, Audit Report Lag, dan Audit Tenure terhadap Integritas Laporan Keuangan : (Studi Empiris Pada Perusahaan Sektor Teknologi yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2021-2022) - Desy Purnamasari; Intan Rizkia Chudri; Nurul Aflah (AKUNTANSI 45, 2024)
Objective in the study are Financial Distress, Audit Report Lag, and Audit Tenure are influential in a way simultaneous And in a way Partial to Integrity Report Finance In Sector Companies Technology listed on the Indonesian Stock Exchange . Study This is study quantitative . Population in study This a total of 36 samples company sector technology listed on the Indonesian Stock Exchange based on purposive sampling . Data used is secondary data obtained from www.idx.co.id or the company website and other related sites with study This . Technique deep data analysis study This with use analysis multiple linear regression . Based on statistical analysis can concluded that financial distress has an effect positive to integrity report finance . Audit report lag and audit tenure do not influential to integrity report finance .